Epidemiological characteristics and outcomes of special-cause burns: analysis of 33,619 burn patients in a major regional burn center in China from 2004 to 2021 - Ze Li; Meijun Jiang; Maomao Xi; Weiguo Xie (BMC, 2024)
Abstract Special-cause burn injuries are usually more severe and difficult to manage, and often contribute to a high mortality in severely injured patients. The aim of this study was to present the epidemiological characteristics of special-cause burn in a major regional burn center in China between 2004 and 2021 and determine the risk factors associated with the mortality of burn patients. A total of 33,619 burn patients were included the study, among which 4,452 (13.2%) were special-cause burn patients. Compared to the thermal burn group, the special-cause burn patients were usually male, elder, married and III-IV degree of burn with onset of upper extremity in summer and autumn. Moreover, a greater proportion of patients in the special-cause burn group underwent surgical treatment and amputation and had a higher median hospital stay and treatment costs. During the multivariate logistic regression, older age, male, unmarried, winter, III-IV degree of burn, ≥ 3 burn sites, and larger total body surface area (TBSA) of burn were significantly associated with higher burn mortality (all P < 0.05), however, patients with special-cause burn injuries have not increased odds for mortality (P > 0.05). These results suggested that special cause-burn patients suffer more severe injuries, resulting in longer hospital stays and higher health care expenditures, but it did not significantly increase the mortality risk. Therefore, burn clinicians should not only have the responsibility to cure burns, but also need to know and popularize burn epidemiological characteristic and precaution.